An evaluation of the effect of coaching on the empowerment of middle managers in the retail sector : a lifelong learning perspective - Fourie, Stefan Steyn (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.